Microwave Liquefaction of Crystallized Jordanian Honeys and Its Impact on Quality Parameters - Al-Ghzawi, Abd Almajeed; Zaitoun, Shahera; Rababah, Taha; Samarah, Nezar; Bin Zaidan, Akram; Yucel, Sevil; Fish, Huda (AMER CHEMICAL SOC, 2026)
Crystallization (granulation) is a common and commercially undesirable phenomenon in honey, as consumers generally prefer liquid products. Conventional thermal treatments can liquefy crystallized honey, but are often associated with deterioration of quality sensitive attributes. In this study, microwave liquefaction was evaluated as an alternative to conventional water bath heating (65 degrees C for 25 min), and its effects on the quality of three Jordanian unifloral honeys (Centaurea, Ballota, and Echinops) were assessed. Crystallized honeys were subjected to microwave treatment at three nominal power levels (30, 60, and 90%) using systematically optimized power and time combinations specific to each botanical origin, and the outcomes were compared with conventional heating. Microwave processing achieved complete crystal dissolution in all honey types, with liquefaction time decreasing as microwave power increased and varying according to botanical origin, whereas conventional heating resulted in incomplete crystal removal under the applied conditions. Both processing methods caused moderate reductions in moisture content, pH, total phenolic content, and enzymatic activities (diastase and invertase). However, these changes were consistently less pronounced following microwave treatment. Total soluble solids, electrical conductivity, and sugar composition were largely unaffected by either method. Although hydroxymethylfurfural content increased after thermal processing, all values remained within Codex specified limits. Overall, the results demonstrate that botanical origin dependent optimization of microwave liquefaction enables rapid and effective decrystallization while better preserving key quality attributes compared with prolonged conventional heating. These findings support microwave processing as a controllable alternative for honey liquefaction within regulatory limits, while emphasizing the need for honey specific optimization to ensure consistent quality preservation across different botanical origins.
Keywords: ANTIOXIDANT ACTIVITY; PHYSICOCHEMICAL PROPERTIES; THERMAL-TREATMENT; TEMPERATURE; CAPACITY; STORAGE; TIME; Chemistry